p-Coumaroyl and feruloyl arabinoxylans from plant cell walls as substrates for ruminal bacteria. - Akin, D E (1993)
Growth of the ruminal bacteria Ruminococcus flavefaciens FD1, Selenomonas ruminantium HD4, and Butyrivibrio fibrisolvens 49 was limited by ester-linked feruloyl and p-coumaroyl groups. The limitation of growth on phenolic acid-carbohydrate complexes varied with individual bacteria and appeared to be influenced by ability to hydrolyze carbohydrate linkages.